Neoliberalism and civil welfare provision in Turkey: the case of deniz Feneri aid and solidarity association - Aydoğmuş, Ümit. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This thesis suggests that, the civil welfare provision organizations and their conceptions of poverty and methods of poverty alleviation create new power relations, subjectivities, and new relations among these subjects, in contemporary Turkey. To analyze this civil power, that usually lays beyond the state, and its complex relations with neoliberalism, global and local financial and political processes; I conducted an organizational fieldwork in an international civil poor relief organization, the Deniz Feneri Aid and Solidarity Association, between 2005 and 2007. In this fieldwork, I focused on the conceptions of poor and poverty, charity, and volunteerism, and their transformations, the current organizational, technological and human power of the association, and organizational decision making processes in its poverty alleviation activities. I also observed that the representations of the poor and poverty also create the charitable and the volunteer subjectivities in the association. Furthermore, by relating the poor, the charitable and the volunteer, the association dislocates the inequalities and power relations among these subjects and their classes, and it reproduces these power relations in a particular civil setting within a neoliberal polity. Hence, this thesis suggests that civil welfare provision organizations represent particular political groups’ discourses of poverty and the poor in Turkish public, create new channels to represent themselves, and furbish these political communities’ understanding of society, family, state, assistance, poverty and citizenship with neoliberal values, beliefs and mores in contemporary Turkey.
Keywords: Poor -- Turkey.; Poverty -- Turkey.; Public welfare -- Turkey.; Social service -- Turkey.